2014
DOI: 10.2147/pi.s46647
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of patient adherence support: a systematic review of the role of pharmacists and doctors

Abstract: We conducted a systematic review of adherence support programs involving doctors and pharmacists. We searched MEDLINE ® , Embase, International Pharmaceutical Abstracts, PsycINFO ® , and CINAHL using the keywords "pharmacist" or "doctor" and "adhere*" or " compli*" and "randomized controlled trials". We found 89 studies involving pharmacists; in contrast, only 14 studies involved doctors. The roles of pharmacists and doctors ranged from providing education and counseling to adjusting treatment. Most interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…The intervention was based on theoretical models and guidelines and the interview protocol contained pre-defined questions and relevant knowledge items. Moreover the protocol stimulated pharmacists to ask about patient opinions, for example by asking “What do you think of getting this medicine?” and to tailor counseling to patients' needs which is important to improve adherence (Andersson et al, 2014). Our study also has its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention was based on theoretical models and guidelines and the interview protocol contained pre-defined questions and relevant knowledge items. Moreover the protocol stimulated pharmacists to ask about patient opinions, for example by asking “What do you think of getting this medicine?” and to tailor counseling to patients' needs which is important to improve adherence (Andersson et al, 2014). Our study also has its limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Educational meetings can change professional practice, 141 and while they have been effective in supporting practitioners manage nonadherence issues in asthma, training for HCPs involved in medication adherence is generally lacking. 142 Arranging educational events at national/international conferences or local study days focussing on best adherence practice, practitioner communication skills and updating and refreshing glaucoma knowledge will provide HCPs with the tools to address adherence better in practice. Practitioners are also encouraged to follow professional body guidelines and recommendations to aid in prescribing and management decisions.…”
Section: Promotion Of Glaucoma Awareness and Educationmentioning
confidence: 99%
“…37 This has substantive implications for the patient's health outcomes. Thorough reviews from Haynes et al 38 and from Andersson et al 39 have identified improved doctorpatient communication as critical to improved adherence to drug regimes, with consequent benefits in health outcomes.…”
Section: Behavioural Mechanismsmentioning
confidence: 99%
“…A number of interventions shaped by behavioural insights have been shown to be effective. These include shorterterm regimens; fewer doses per day; easy-to-use packaging; reminders; tailoring; patient education; and patient satisfaction measurement (see reviews from Haynes et al 38 and Andersson et al 39 ). One idea to ensure individuals finish their regime is to make the final few pills in different colours to the rest and to state that these needed to be taken last (Kesselheim et al 124 ).…”
Section: Increasing Adherence To Medicationmentioning
confidence: 99%